ANALISIS PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DAN KEPUASAN KERJA PADA PEMERINTAH KOTA SEMARANG - Lilis Setyowati; Purwantoro Purwantoro (MEDIA, 2013)
job satisfaction in the local government of Semarang. The hypothesis of this study is whether the positive effect of budget participation on performance and job satisfaction manajeral local government of Semarang. The data in this study is a questionnaire data. A total of 33 respondents from a sample of instansi badan kesbangpol & linmas, dinas perindustrian dan perdagangan, dinas koperasi, dinas kelautan dan perikanan, satpol pamong praja, dan kantor perpus & arsip daerah. Analysis of the hypotheses used in this study is a simple regression. Results of this study indicate that no budgetary participation has a positive effect on managerial performance and job satisfaction of the local government of Semarang.